Simultaneous Quantification of 18 Bioactive Constituents in Tripterygium wilfordii Using Liquid Chromatography-Electrospray Ionization-Mass Spectrometry - Zeng, Feng; Wang, Wei; Guan, Shuhong; Cheng, Chunru; Yang, Min; Avula, Bharathi; Khan, Ikhlas A.; Guo, De-an (Planta Medica, 2013)
A liquid chromatography–electrospray ionization–mass spectrometry method with multiple reaction monitoring was established for simultaneous quantification of 18 bioactive constituents from the stem and root of Tripterygium wilfordii Hook. f. collected from different places in China and various commercial preparations. The chromatographic separations were achieved on an Agilent Poroshell SB-C18 column (150 × 4.6 mm, 3.5 µm) with gradient elution using acetonitrile and 0.03 % formic acid aqueous solution in 45 min. Detection was performed in the positive ionization mode by monitoring the precursor–product combination. The validation of the method included tests of linearity, sensitivity, precision, repeatability, stability, and accuracy. All calibration curves showed good linearity (r > 0.9990) within the test range. The established method showed good precision and accuracy with intraday and interday variations of 2–5 % and 1–4 %, respectively, and recoveries of 95.5–104.5 %.
Keywords: Tripterygium wilfordii; sesquiterpenoid alkaloids; diterpenoids; triterpenoids; HPLC-ESI-MS; multiple reaction monitoring; Celastraceae